Typological and Digital Study of Grinding Stone Tool from Almyrolakka at Pylos - Καλιντέρης, Κωνσταντίνος-Παναγιώτης (Πανεπιστήμιο Πελοποννήσου, 2023)
In this thesis Photogrammetry and Relative Dating were applied on a grinding stone tool found on Almyrolakka beach in the area of Pylia, Messenia, within the framework of Geoarchaeological Program of Pylos. Relative Dating was applied in accordance to the typological comparison of a similar grinding stone tool from the nearby site of P.O.T.A. Romanos and it concluded that the grinder studied in this thesis belongs to the final phase of Early Helladic period. This period in Mainland Greece spans from 3.000 B.C. to 2.000 B.C. and gradually evolves from a local to multi-regional culture, with its main characteristic, the Corridor Houses built for communal feasting and the mobilization and circulation of staple goods. This brief period of prosperity promoted an “international spirit”, where contacts and exchange of ideas with Cyclades, Minoan Crete and Western coast of Asia Minor were frequent. This international culture ceased to exist due to climatic reasons and reorganized in a new local basis, in a period that civilization in the Fertile Crecent was in turmoil. Apart from dating, this thesis also dealt with the novel technologies for the preservation and promotion of material cultural heritage, in which the grinding stone tool belongs. In order to achieve it, Agisoft Metashape software was applied for the extraction of a final 3D model of the Almyrolakka grinder, pointing out its surface details and priorities, which included scratches, blots and white markers. The grinder’s digitization was applied in order to achieve direct contact between the audience and the artifact and through the application of Agisoft Metashape software, to permit examination of its surface priorities, contributing in the overall research and social impact. Furthermore, the work may be enhanced with the supplementation of 3D printers for the fulfillment of experiential learning, through the sense of touch.
Keywords: Πέτρινα εργαλεία -- Ελλάδα -- Αλμυρόλακκα (Πύλος); Πέτρινα εργαλεία -- Ελλάδα -- Αλμυρόλακκα (Πύλος) -- Ανάλυση; Τριπτήρας, λίθινος -- Ελλάδα -- Αλμυρόλακκα (Πύλος); Τριπτήρας, λίθινος -- Ελλάδα -- Αλμυρόλακκα (Πύλος) -- Ανάλυση; Φωτογραμμετρία; Αρχαιολογική χρονολόγηση; Αρχαιολογία -- Μεθοδολογία; Photogrammetry; Stone Tools; Early Helladic; Grinders; Φωτογραμμετρία; Λίθινα Εργαλεία; Πρώιμη Ελλαδική; Τριπτήρες